Comparative analysis on selection and synthesis of multiple input converters: a review. Issue 4 (1st March 2020) - Hema Chander, Allamsetty; Kumar Sahu, Lalit; Ghosh, Subhojit; Gupta, Krishna Kumar
Abstract : Power electronics converters for DC–DC conversion are extensively used in various applications. Further, with an increase in demand for integrating multiple sources with distinct I – V characteristics, a change over from single input DC–DC converters to multiple input converters (MICs) has been observed in the recent past. MICs are widely used for effective integration of energy sources in various applications ranging from milliwatt to megawatt power levels and millivolt to several kilovolts of voltage levels. The combination of sources with respective energy buffering units allow for a new configuration and topology, which are quite confusing and challenging to pick one for a specific application. MICs are categorised based on their characteristics, and each category has its pros and cons depending on the application. Further, this study categorises and comprehensively reviews the MICs based on their characteristics. In this regard, this study aims to provide a clear picture of MICs and the general rules and framework for the selection of MIC topology for a specific application. Also, the key features and limitations of a few recently proposed MICs, followed by the selection of MICs for different applications are discussed.